IMPROVING THE METHOD OF ENDOSCOPIC REMOVAL OF SUPERFICIAL POLYPOID AND NON-POLYPOID FORMATIONS OF THE GASTROINTESTINAL TRACT (World Bulletin of Public Health, 2024)
The article presents a developed method for endoscopic removal of polypoid neoplasms of the gastrointestinal mucosa. The technical aspects of the developed method of endoscopic removal of superficial polypoid and nonpolypoid neoplasms of the gastrointestinal tract are the formation of a roller under the formation by injection of the proposed combined gel substance to ensure a local hemostatic effect, improve control over the intervention area, as well as the use of high-energy laser exposure to increase the radicality of removal regardless of the localization, shape and size of the formation.
Keywords: polypoid neoplasms; gastrointestinal tract; endoscopic interventions